If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + (2t + 4) = -5 Reorder the terms: t + (4 + 2t) = -5 Remove parenthesis around (4 + 2t) t + 4 + 2t = -5 Reorder the terms: 4 + t + 2t = -5 Combine like terms: t + 2t = 3t 4 + 3t = -5 Solving 4 + 3t = -5 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3t = -5 + -4 Combine like terms: 4 + -4 = 0 0 + 3t = -5 + -4 3t = -5 + -4 Combine like terms: -5 + -4 = -9 3t = -9 Divide each side by '3'. t = -3 Simplifying t = -3
| 8x/3-5x/4=-13 | | 5/25=y/85 | | -(5b+5)-5=1-(5b-1) | | -36=4w | | 11=3-7x | | X^3-2X+0.5=0 | | X^3-2X-0.5=0 | | 22=2c | | -2(2(2)-4)=-4(-2+2) | | 4x^2+9x-2=0 | | .90x+.52(2-x)=.10(-118) | | 3x-16cm=200cm | | 7x+2[3(1-x)]=14 | | 3(t+2)-(3t-3)=2(3t-4)-13 | | 3(t+2)-(3t-3)=2 | | 64=8n | | (x+3)-2c-(1-3x)=2 | | 6w^3-28w+16=0 | | .5y+2=.8y-.3 | | x=4x+96 | | 2w-6m=50m | | -8(-1)-(3(-1)+6)=4+-1 | | -7=3(x-5)-x | | x-13x+10x=50-6 | | -17+2x=6-x | | X=10+-2X | | (x+1)(x+2)=2x | | 6x+14=2x | | 0.25(q-12)=4 | | 10n=4n+5+5n | | 2x+1+5X-11=4X | | 7-3(2y+4)=1 |